The Use of Single Picture Media to Improve Students’ Writing Skill Through Writingdescriptive Text at Tenth of SMA Darussalam Banyuwangi - Moh Mahmud (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
In Indonesia English is considered as the first foreign language. English is one of the international languages ​​spoken by many people in the world. Learning English is important because by knowing English well it will be easier for them to understand every writing of information in English. Teaching English should include four language skills: listening, speaking, reading and writing. This research was conducted using classroom action research as a methodology of this research. There are three meetings during the research (pre-cycle, cycle 1, cycle 2, consisting of planning, acting, observing, and reflecting). Researchers used written tests to measure students' skills in descriptive text writing after treatment, use of observations to monitor student activity during the teaching and interviewing process to obtain information and verify the data. The results of quantitative data on the application of the technique to see a single image can improve the writing skills of students in grade X4 SMA Darussalam Blokagung Tegalsari Banyuwangi. This can be seen from the results of the test evaluation and observation results are always increasing during the implementation of this technique is done. Can improve writing skills as well. It can be concluded that the use of a single image can effectively improve students' writing skills. In addition, the single image is also in good design and good themes, so that students are more motivated and enjoy the learning process